The effects of an IPS-based IPE program on interprofessional socialization and dual identity development. - Khalili, Hossein; Orchard, Carole (Journal of Interprofessional Care)
The purpose of this study was to assess the effect of an interprofessional socialization (IPS) based interprofessional education (IPE) program intervention on health professions students' IPS process and dual identity development. Despite the growing acknowledgment of IPS in recent literature, there is a paucity of research investigating socialization processes learners move through in order to develop dual identity – professional and interprofessional. A concurrent embedded mixed-method design was used. One hundred and eight pre-licensure students from seven different health professions completed the IPS program intervention. Latent Growth Curve (LGC) modeling and thematic content analysis were used to analyze the quantitative and qualitative data, respectively. A significant and consistent growth rate in dual identity was found among the participants. The thematic analysis resulted in four emerging themes (uniprofessional education as a barrier, IPS program as an eye-opener, learning to collaborate, and collective unified team). The integrated findings provide support for the use of the interprofessional socialization framework.